My Mother Is Not My Friend: Sebuah Pembongkaran Mitos Relasi Ibu dan Anak Perempuan - Hayati, Irma Vania Nurmala; Karsono, Sony; Lasmono, Hari K. (Faculty of Psychology, Universitas Surabaya, 2007)
This study is a biographical investigation depicting the life of a girl named Raisa, especially concerning her conflict with her mother, Hartini. Results reveal some interesting facts as follows. Firstly, Raisa’s life is connected with the former life, desires, hopes, and demands of Hartini. Conflicts arose due to differences in hopes and calculation criteria between them, and difference between myth beliefs and real facts they have to face. Secondly, Raisa who seems to be trapped in a chaotic family and has become a victim, actually is in a right position and gains many advantages. Thirdly, the truth about Hartini’s autobiography has a greater strength than objective facts of her life and brings about benefits, not only for Hartini, but for the whole family as well. Penelitian ini adalah suatu kajian biografi yang menuturkan kisah hidup seorang anak perempuan bernama Raisa, khususnya yang terkait dengan konflik antara dirinya dan ibunya— Hartini. Hasil penelusuran biografis ini mengungkap beberapa hal menarik berikut. Pertama, kehidupan Raisa terkait dengan masa lalu, cita-cita, harapan, dan keinginan Hartini. Konflik muncul akibat adanya perbedaan pengharapan dan kriteria kalkulasi di antara mereka, serta adanya perbedaan mitos yang diyakini dengan kenyataan yang harus dihadapi. Kedua, Raisa yang di satu sisi tampaknya terjebak dalam situasi keluarga yang penuh konflik dan menjadi korban, sebenarnya justru berada pada posisi yang tepat dan mendapatkan banyak keuntungan. Ketiga, kebenaran autobiografis Hartini mempunyai kekuatan yang lebih besar daripada kenyataan objektif akan kehidupannya dan membawa keuntungan, tidak hanya bagi Hartini saja, melainkan juga bagi seluruh keluarganya.